ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT STRES PADA PASIEN HEMODIALISA DENGAN PENYINTAS COVID 19 DI RSUD KOJA - Afifah Jihan Ramadhan, (2021)
Stress is the suppression of one's feelings when experiencing problems from outside and from within the individual which causes the balance of life to be disturbed, thus requiring a person to adapt physically and psychologically. One of the conditions that can cause stress is hemodialysis, which is a treatment for someone who has decreased kidney function. This study aims to analyze the factors that influence stress levels in hemodialysis patients with covid 19 survivors at Koja Hospital. This study uses a cross sectional design anf done at 39 sample with the sampling method of saturation sampling. Based on statistical tests, it is known that the factors that influence stress levels in hemodialysis patients with Covid 19 survivors are length of hemodialysis (P value = 0.14), frequency of undergoing hemodialysis (P value = 0.003), and family support (P value = 0.002). Factors of age, gender, occupation, income have no effect on stress levels in hemodialysis patients with Covid 19 survivors at Koja Hospital. It is hoped for hospital agencies this research is used as input on factors that affect stress levels, so that the nursing care provided includes bio-psycho-social.